Analisis Dampak Investasi Dan Konsumsi Pada Sektor Energi Terbarukan Dalam Pembangunan Ekonomi Berkelanjutan - Nasution, Ade Irma sofyan; Harahap, Isnaini; Harahap, Muhammad Ikhsan (ITB AAS INDONESIA Surakarta, 2024)
This research aims to determine the impact of investment and consumption in the renewable energy sector in sustainable economic development. This research uses a quantitative method of multiple linear regression analysis processed with Eviews 13 software. This research uses renewable energy sector investment data in 2017-2023 with data sources from the Ministry of Energy and Mineral Resources and the Ministry of EBTKE, renewable energy consumption data sourced from the World Bank as well as emission reduction data as a result of the existence of renewable energy in accordance with the 7th pillar of the SDGs. This research found results where there is a negative relationship between investment and reducing CO2 emissions and a positive relationship between consumption and reducing CO2 emissions. However, partially and simultaneously all independent variables have an effect on reducing CO2 emissions. This is in accordance with data from the Ministry of Energy and Mineral Resources, currently the renewable energy mix is only 13%, this is weakening due to the pandemic in 2020-2022. So, to increase energy security in the future, there must be increased investment in renewable energy in sustainable development because conventional energy sources are increasingly depleted and environmental pollution can disrupt ecosystems and economic systems.